Food‐Poisoning Bacteria Employ a Citrate Synthase and a Type II NRPS To Synthesize Bolaamphiphilic Lipopeptide Antibiotics - Dose, Benjamin (John Wiley and Sons Inc., 2020)

(untitled) (Angew Chem Int Ed Engl)
Mining the genome of the food‐spoiling bacterium Burkholderia gladioli pv. cocovenenans revealed five nonribosomal peptide synthetase (NRPS) gene clusters, including an orphan gene locus (bol). Gene inactivation and metabolic profiling linked the bol gene cluster to novel bolaamphiphilic lipopeptides with antimycobacterial activity. A combination of chemical analysis and bioinformatics elucidated the structures of bolagladin A and B, lipocyclopeptides featuring an unusual dehydro‐β‐alanine enamide linker fused to an unprecedented tricarboxylic fatty acid tail. Through a series of targeted gene deletions, we proved the involvement of a designated citrate synthase (CS), priming ketosynthases III (KS III), a type II NRPS, including a novel desaturase for enamide formation, and a multimodular NRPS in generating the cyclopeptide. Network analyses revealed the evolutionary origin of the CS and identified cryptic CS/NRPS gene loci in various bacterial genomes.